Bidirectional astrocytic GLUT1 activation by elevated extracellular K+. Issue 4 (5th December 2020) - Fernández‐Moncada, Ignacio; Robles‐Maldonado, Daniel; Castro, Pablo; Alegría, Karin; Epp, Robert; Ruminot, Iván; Barros, Luis Felipe
Abstract: The acute rise in interstitial K + that accompanies neural activity couples the energy demand of neurons to the metabolism of astrocytes. The effects of elevated K + on astrocytes include activation of aerobic glycolysis, inhibition of mitochondrial respiration and the release of lactate. Using a genetically encoded FRET glucose sensor and a novel protocol based on 3‐ O ‐methylglucose trans‐acceleration and numerical simulation of glucose dynamics, we report that extracellular K + is also a potent and reversible modulator of the astrocytic glucose transporter GLUT1. In cultured mouse astrocytes, the stimulatory effect developed within seconds, engaged both the influx and efflux modes of the transporter, and was detected even at 1 mM incremental K + . The modulation of GLUT1 explains how astrocytes are able to maintain their glucose pool in the face of strong glycolysis stimulation. We propose that the stimulation of GLUT1 by K + supports the production of lactate by astrocytes and the timely delivery of glucose to active neurons. Main Points: The astrocytic glucose pool does not reflect the stimulation of glycolysis by high K + . A novel minimally invasive assay shows that K + activates GLUT1. Astrocytic GLUT1 activation by K + is poised to support glycolysis in both astrocytes and neurons.